Peristaltic Pumping of Two-Layered System in a Channel with full Slip and Temperature Jump Conditions - Kumar, S. Vijaya; Srinivas, A. N. S. (Journal of Applied Nonlinear Dynamics, 2026)
The present article investigates peristaltic transport of two immiscible fluids in a channel with the influence of slip and temperature jump conditions at boundary walls. The peristaltic pumping of a non-Newtonian fluid occupies in core region and Newtonian fluid in peripheral region. The exact solutions for flow quantities such as pressure rise, stream function and temperature field in both regions are obtained. The effects of different pertinent parameters on variation of pressure rise along the mean flow rate and temperature distribution are analyzed through graphs. The variations in the interface due to the change in physical parameters are also analyzed. It is noticed that the slip parameters have significant effect on pressure rise and temperature distribution. It is noticed that the temperature profile decreases with increasing first slip parameter and also observed that the temperature profiles increases with increasing values of second slip parameter.